Intensive animal farming operations and outbreaks of zoonotic bacterial diseases in Ukraine - T. Tsarenko; L. Korniienko (Regulatory Mechanisms in Biosystems, 2021)
In Ukraine zoonoses are a permanent threat to human health, some of them are bacterial diseases associated with farm animals. Complete avoidance of outbreaks of bacterial zoonoses is not possible but it is appropriate to study them to reduce the risks of transmission of zoonosis pathogens from industrial farms to the human population and the environment. The article highlights the results of a literature review on the potential role of industrial livestock farms in the spread of major bacterial zoonoses in Ukraine. About half of all of the country’s farmed animals are kept on farms using industrial technology; more than half of the establishments are classified as medium and large. The technology of keeping animals on such farms contributes to the development of diseases of obligate hosts caused by fecal bacteria. The systematic search and selection of literary sources, which are relevant to the topic of the study were carried out. The vast majority of analyzed publications are published in Ukrainian in local peer-reviewed scientific journals. An analysis of open-access official statistics from the state authorities of Ukraine was also conducted. The authors analyzed statistics and scientific papers published over the last 10–15 years discussing the outbreaks of food-borne zoonoses among humans and the studying their pathogens (Campylobacter spp., Salmonella spp., Escherichia coli (STEC strains), Listeria spp.) on industrial livestock farms. The main source of Campylobacter spp. and Salmonella spp. distribution are industrial poultry, including broilers and chickens, respectively. The STEC strains E. coli carriers are various types of farm animals, including cattle and pigs. The majority of infections documented in Ukraine are cases of salmonellosis in humans and animals. Despite reports of a significant prevalence of campylobacteriosis, colibacillosis and listeriosis in livestock farms, their association with outbreaks of food-borne zoonoses in humans remains poorly understood. The concept of an industrial livestock farm involves a permanent presence of a risk of outbreaks of bacterial zoonoses and their rapid spreading to the human population. This is due to concentrated maintenance of animals, standardized feeding, the priority of achieving the highest productivity of animals and economic indicators. Under such conditions, disturbance of hygienic norms and technologies significantly increases the risk of bacterial zoonoses on industrial farms. It is important to enforce the continuous control of the level of microbial pollution of farms, animal health, hygiene of milk production and processing, meat, eggs, etc. Farms have a negative impact on the ecological welfare of the surrounding territories. The problem of spread of antibiotic-resistant strains of bacterial zoonoses is a very serious one. Efforts for the formation of a national system of epidemiological supervision over bacterial zoonoses, comprising epidemiological, epizootological, ecological, microbiological, serological and molecular genetic monitoring, as well as the development on this basis of effective prophylactic and anti-epidemic measures are relevant and necessary.